In Search of the Temples of YHWH of Samaria and YHWH of Teman - Na’aman, Nadav (Journal of ancient Near Eastern religions, 2017)
The Kuntillet ‘Ajrud inscriptions mention blessings by the names of YHWH of Samaria and YHWH of Teman. Like all ancient Near Eastern gods, these two regional gods must have had central temples. This article examines their possible locations and suggests that the combination of the Kuntillet ‘Ajrud inscriptions with the eighth-century prophecies of Amos and Hosea holds the key for identifying these. In light of a detailed analysis of Hosea’s and Amos’ prophecies, it is further suggested that YHWH of Samaria was the name of the major God of the Kingdom of Israel and his main temple was located at Bethel, and that YHWH of Teman was the name of the God of the southern desert regions and his temple was located at Beer-sheba. Israelite traders who traveled southward probably visited the latter god’s temple, offered him sacrifices, made vows to repay him if they succeed in the expedition, and thus turned him to be their patron god during their travel in the desert region. This suggested identification explains why the Judahite cult place of Beer-sheba appears in Amos’ prophecy alongside the Israelite sanctuaries of Bethel, Gilgal, and Dan.